Mechanical behaviour of WAAM ER70S steel at elevated temperatures - Peh, Shannon Zhi Qing (Nanyang Technological University, 2024)
This report presents an experimental study on the mechanical behaviour of WAAM (wire and arc additive manufactured) ER-70S steel in and after exposure to fire. Eighty tensile coupon specimens were extracted from WAAM printed plate, with nominal thickness of 3mm and 8mm, and the orientation parallel and perpendicular to the printing direction. The performed investigations include 3D and laser scan for geometric analysis, post-fire testing with temperature ranged from 30°C - 1000°C, and in-fire testing with temperature ranged from 30°C - 600°C. The degrade of mechanical properties of post-fire scenario is examined by standard BS5950-8, while the retention factor of in-fire scenario is verified by standard BS EN 1993-1-2. Experimental result indicated current design code of carbon steel may underestimate the reduction of mechanical properties for both in and after fire, especially in terms of elastic modulus and yield stress.